Fractionation, Physicochemical Analysis, and Oil Extraction Efficiency of Melon Seeds - Rakhmatulla ugli, Mikhliev Temurbek (American Journal of Botany and Bioengineering, 2025)
Melon seeds are considered a promising oil-bearing raw material, containing 30–40% lipids and 34–39% proteins on a dry matter basis [1]. Therefore, the processing of melon seeds enables the expansion of the range of vegetable oils belonging to the linoleic group, in which the content of unsaturated fatty acids reaches up to 85% [2]. This is of particular importance for healthy human nutrition, as animal fats still predominate in the daily diet of the world population.